Effect of pioglitazone therapy on high sensitive C-reactive protein and lipid profile in diabetic patients with renal transplantation; a randomize clinical trial - Rana Arashnia; Kobra Roohi-Gilani; Hamidreza Karimi-Sari; Niloofar Nikjoo; Ali Bahramifar (Society of Diabetic Nephropathy Prevention, 2015)
Background: Inflammation has a major role in disease lead to renal failure and diabetes mellitus, controlling inflammation in diabetic kidney receivers could decrease morbidity and mortality. Objectives: This study designed for evaluating the efficacy of pioglitazone on C-reactive protein and lipid profile in diabetic kidney transplant receivers. Patients and Methods: In this double blinded clinical trial, 58 diabetic renal transplant receivers, in first month after transplantation, randomized into two groups; receiving insulin and pioglitazone (15 mg tablet daily, group A); and insulin and placebo (group B). Blood pressure, weight, body mass index (BMI) and laboratory data compared in before and after 4-month treatment in two groups by SPSS. Results: Fifty-eight patients with mean age of 44.15 ± 2 years included. There were no significant difference between groups in demographic data and other baseline measured variables (P > 0.05) .The mean weigh and BMI were slightly increased in group A and decreased in group B. The mean hs-CRP was decreased 4.82 mg/dL in group A and 1.93 mg/dL in group B (P = 0.007). The mean total serum cholesterol was significantly decreased 34 mg/dL in group A and 18.07 mg/dL in group B (P = 0.027). The mean serum HDL-C was significantly increased 13.31 mg/dL in group A and 5.89 mg/dl in group B (P < 0.001). Conclusions: Pioglitazone seems to be a safe drug for reducing serum lipids and CRP in kidney transplant receivers with diabetes mellitus in short term. Long term effect of this drug could be evaluated in future studies.